The Qur'an and Self-Actualization: Thematic Verses on the Pillars of Islam from Abraham Maslow's Perspective: Al-Qur’an dan Aktualisasi Diri: Ayat-ayat Tematik tentang Rukun Islam Perspektif Abraham Maslow - Nurrahim, Hifsa; Zamimah, Iffaty (Institut Agama Islam Negeri Kerinci, 2023)
This article discusses self-actualization with the progress of civilization and the rapid growth of technology giving rise to many offers of ways of life so as to create a confusing situation and individuals fail to make meaning of their lives. Maslow with the theory of the hierarchy of human needs through self-actualization can understand and accept themselves so that they act better in the future. The pillars of Islam as a coaching system of ideal character building and training to achieve self-actualization. Based on this statement, this paper tries to examine self-actualization through the interpretation of the verses of the Pillars of Islam with the hierarchy of needs theory. This research uses qualitative studies with literature studies. The method of data collection is the documentation method, primary data sources from the literature of the book of tafsir and psychology books, secondary data sourced from journals and scientific papers analyzed by descriptive-analysis. The approach used is the psychological approach of Abraham Maslow's hierarchy of needs theory. The results of this study are self-actualization through the pillars of Islam in the Qur'an can form a better Muslim personality in terms of physical and mental, the significance of the verse and the link to Abraham Maslow's hierarchy of needs theory is QS. al-Anbiyā [21]: 25 about monotheism to Allah Swt. can be linked to the theory of the initial stage (physiological) and the final stage (self-actualization), QS. al-Ankabūt [29]: 45 about prayer preventing evil deeds and dislikes covers the needs of the second level (security), third (love and affection) and self-actualization, QS. al-Baqarah [2]: 183 about fasting as a path to taqwa in various fields of life covers the first stage of the third, fourth (self-esteem) and self-actualization, QS. al-Taubah [9]: 103 about zakat which purifies covering the second, third and self-actualization stages, QS. al-Baqarah [2]: 197 about Hajj the highest need (self-actualization) to achieve the degree of taqwa.